2005
DOI: 10.1086/429491
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with HIV and Hepatitis C Virus among Injection Drug Users in Southern China

Abstract: HCV is highly prevalent in IDUs throughout southern China. In Guangxi, HIV infections are the result of parenteral and sexual transmission, and, therefore, all IDUs are at high risk of coinfection with HIV and HCV. Molecular tracking of HCV may be a more sensitive predictor of the future spread of the HIV-1 epidemic than is HIV subtyping. This study emphasizes that, without implementation of injection prevention and primary substance abuse programs in China, the extent and effect of coinfection with HIV and HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
94
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 28 publications
14
94
3
Order By: Relevance
“…Although HCV and HSV-2 are both relatively uncommon in the general Chinese population (31,(19)(20)(21), a high prevalence of HCV coinfection was observed among the study subjects who had contracted HIV through drug injections and plasma/blood donation or transfusion but a high prevalence of HSV-2 coinfection was also observed among those who had become HIV-infected through heterosexual transmission. Previous studies have reported that HCV infection is prevalent among former plasma donors and injection drug users and that HSV-2 infection is prevalent among commercial sex workers in China (15)(16)(22)(23)(24). In this study, geographic region was also independently correlated with HCV and HSV-2 coinfection among HIV/AIDS patients.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Although HCV and HSV-2 are both relatively uncommon in the general Chinese population (31,(19)(20)(21), a high prevalence of HCV coinfection was observed among the study subjects who had contracted HIV through drug injections and plasma/blood donation or transfusion but a high prevalence of HSV-2 coinfection was also observed among those who had become HIV-infected through heterosexual transmission. Previous studies have reported that HCV infection is prevalent among former plasma donors and injection drug users and that HSV-2 infection is prevalent among commercial sex workers in China (15)(16)(22)(23)(24). In this study, geographic region was also independently correlated with HCV and HSV-2 coinfection among HIV/AIDS patients.…”
Section: Discussionsupporting
confidence: 48%
“…Worldwide it is estimated that 10-30% of the 40 million people infected with HIV are co-infected with HCV due to similar transmission routes between HIV and HCV (14). In China, high prevalence of HIV and HCV coinfection has been reported among injection drug users (IDU) and plasma/blood donors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Yunnan Province, which borders Guangxi Zhuang Autonomous Region in the west, have found high HCV co-infection rates in HIV-1 positive drug users [39] . Previous epidemiological studies in Guangxi not only found similar high rates of HCV co-infection in HIV-1 positive drug users, but a high HCV prevalence (72%), incidence (37.8 per 100 person years) in all heroin users enrolled in the study [40] . To determine the clearance rate of HCV RNA and study factors that influence clearance, serum from a large cohort of heroin users from Guangxi Zhuang Autonomous Region, southern China was qualitatively tested for HCV RNA.…”
Section: Rapid Communicationsupporting
confidence: 53%
“…Study participants from Pingxiang have been followed since September 1999 while participants from Binyang have been followed since January 2000. The informed consent procedure was described previously [40] . Briefly, at each visit, participants underwent blood draw and personal interviews and were counseled on the results of their serological tests.…”
Section: Study Participantsmentioning
confidence: 99%
“…Genotype 6e showed lower prevalence in Hai Phong and Guangxi and was not found in Yunnan province. transmission routes into consideration and use HCV infection as a prediction marker for HIV infection [Garten et al, 2005]. …”
Section: Page 12/24mentioning
confidence: 99%